The effects of chitosan/miR-200c nanoplexes on different stages of cancers in breast cancer cell lines - (:unkn) unknown (ELSEVIER SCIENCE BV, 2016)
Dysregulation of miR-200c in breast cancer has been associated with migration, epithelial mesenchymal transition (EMT), angiogenesis and metastasis of the tumor cells. Therefore, the modulation of miR-200c offers a promising therapeutic approach in breast cancer. However, the major obstacles in the usage of miRNAs in therapy are their low stability, rapid clearance, and poor cellular uptake. The development of efficient and safe delivery systems is important in effective therapy with miRNA. The purpose of this study was to investigate the therapeutic role of chitosan/miR-200c nanoplexes in angiogenesis, EMT, invasion, and apoptosis in breast cancer cell lines. We found that miR-200c levels were downregulated in various breast cancer cell lines by qRT-PCR After transfection with chitosan/miRNA nanoplexes in the appropriate size (294 nm) and zeta potential (12.3 mV), levels of miR-200c increased and reached the endogenous miR-200c levels in the MCF-7, MDA-MB-231, and MDA-MB-435 cells. While the chitosan/miR-200c nanoplexes decreased angiogenesis, invasion, EMT, and metastasis in the cells, the apoptosis levels increased by 3.1, 1.3, and 3 fold in the MCF-7, MDA-MB-231, MDA-MB-435 cell lines, respectively. Consequently, chitosan is a suitable carrier for miR-200c and formed stable nanoplexes with miR-200c. The effect of the chitosan/miRNA nanoplexes on tumor angiogenesis, EMT, invasion, metastasis, and apoptosis, changed depending on the cell-types. Therefore, during the treatment with the chitosan based miR-200c nanoplexes in breast cancers, the type of tumor cells must be considered. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: miR-200c; Chitosan; Breast cancer; miRNA delivery system; EPITHELIAL-MESENCHYMAL TRANSITION; ENDOTHELIAL GROWTH-FACTOR; CHITOSAN NANOPARTICLES; MICRORNA-200 FAMILY; MIR-200; DELIVERY; INVASION; SUPPRESSION; EMT; ANGIOGENESIS